2006
DOI: 10.1152/physiolgenomics.00206.2005
|View full text |Cite
|
Sign up to set email alerts
|

Distinct pattern of lung gene expression in theCftr-KO mice developing spontaneous lung disease compared with their littermate controls

Abstract: Cystic fibrosis (CF) is caused by a defect in the CF transmembrane conductance regulator (CFTR) protein that functions as a chloride channel. Dysfunction of the CFTR protein results in salty sweat, pancreatic insufficiency, intestinal obstruction, male infertility, and severe pulmonary disease. Most of the morbidity and mortality of CF patients results from pulmonary complications. Differences in susceptibility to bacterial infection and variable degree of CF lung disease among CF patients remain unexplained. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 64 publications
2
31
2
Order By: Relevance
“…3) by RT-qPCR. Furthermore, many of the upregulated genes identified in our study, such as IL-6, IL-8, IL-1B, and IL-1A, have also been identified in other CF tissues (19,23,36,53). However, in recent experiments on CFBEs, the authors report no compelling evidence that mutations in CFTR induce a hyperinflammatory response in CF epithelial cells (20).…”
Section: Proinflammatory Profile Of Cufi-1/nuli-1 Cell Linescontrasting
confidence: 64%
See 1 more Smart Citation
“…3) by RT-qPCR. Furthermore, many of the upregulated genes identified in our study, such as IL-6, IL-8, IL-1B, and IL-1A, have also been identified in other CF tissues (19,23,36,53). However, in recent experiments on CFBEs, the authors report no compelling evidence that mutations in CFTR induce a hyperinflammatory response in CF epithelial cells (20).…”
Section: Proinflammatory Profile Of Cufi-1/nuli-1 Cell Linescontrasting
confidence: 64%
“…Several investigations of CF mouse models have reported overexpression of inflammatory genes in CF lungs (19,23,53) and intestinal tissue (36). However, these observations could not be consistently reproduced in CF bronchial epithelial cell lines or primary culture of CF epithelial cells (20).…”
mentioning
confidence: 99%
“…Overall, CF mice still represent the most useful and costefficient animal model available to study such a multifaceted and devastating disease. We have previously reported that the Cftr-KO mouse model develops spontaneous inflammatory lung disease [39][40][41][42]. In addition, we have recently demonstrated that they also exhibit an imbalance between DHA and AA, similar to CF patients [29].…”
Section: Discussionmentioning
confidence: 99%
“…As we had only two replicates for each sample (too small a number to use methods based on analysis of variance or integral methods, such as RMA or PLIER), we employed the method of consecutive sampling and coincidence test (Guilbault et al, 2006;Novak et al, 2006a;Novak et al, 2006b;Novak et al, 2002). In two-array comparisons, the genes are ordered according to mean signal intensity and grouped in bins containing n consecutive genes (in the present case, n=25).…”
Section: Microarray Analysismentioning
confidence: 99%
“…Four different samples, two dorsal and two ventral, were reverse transcribed, labeled and hybridized to the Xenopus Affymetrix Genechip. Results were analyzed using the Affymetrix Expression Console and MAS5 algorithm, and because we only had two replicates, we employed the method of consecutive sampling and coincidence test (Guilbault et al, 2006;Novak et al, 2006a;Novak et al, 2006b;Novak et al, 2002). The results of this analysis yielded 158 genes as being ventral enriched and 68 genes as being dorsal enriched (see Tables S1 and S2 in the supplementary material).…”
Section: Research Articlementioning
confidence: 99%